1997
DOI: 10.1111/j.1439-037x.1997.tb00494.x
|View full text |Cite
|
Sign up to set email alerts
|

Site Specific Weed Control in Winter Wheat

Abstract: There is much documentation in the scientific literature (e.g. Clay et al. 1999, Hamouz et al. 2006, Gerhards et al. 2012) that weeds are distributed in a patchy manner throughout agricultural fields. An aggregated distribution pattern of weed populations provides opportunity to reduce the herbicide application if site-specific weed management is adopted. Gerhards et al. (2002) achieved herbi-cide savings of 60% and 92% for dicotyledonous and monocotyledonous weeds, respectively, in spring barley (Hordeum vulg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 8 publications
1
32
0
2
Order By: Relevance
“…Site-specific weed management, based on weed distribution maps, can reduce treatment costs as well as herbicide loading in the environment. Several studies on site-specific weed control have shown that this practice is reasonable and it has been applied successfully to various crops, resulting in a considerable reduction of herbicide use and consequently benefits to the environment (Cousens 1987;Thompson et al 1991;Johnson et al 1995;Gerhards et al 1997;Gerhards and Christensen 2003). The German plant protection law requires the use of economic weed thresholds, i.e, critical values above which herbicide treatments are economically viable.…”
Section: Introductionmentioning
confidence: 99%
“…Site-specific weed management, based on weed distribution maps, can reduce treatment costs as well as herbicide loading in the environment. Several studies on site-specific weed control have shown that this practice is reasonable and it has been applied successfully to various crops, resulting in a considerable reduction of herbicide use and consequently benefits to the environment (Cousens 1987;Thompson et al 1991;Johnson et al 1995;Gerhards et al 1997;Gerhards and Christensen 2003). The German plant protection law requires the use of economic weed thresholds, i.e, critical values above which herbicide treatments are economically viable.…”
Section: Introductionmentioning
confidence: 99%
“…Het ruimtelijke patroon van de plantensoort vormt hierbij een belangrijk onderdeel van de beschrijving (Cardina et al, 1997), zeker voor knolcyperus. Onkruidpatronen hebben veelal een plekkerig karakter (Cardina et al, 1997;Gerhards et al, 1997;Heijting et al, 2007  Er mag een maximale oppervlakte van 1 hectare behandeld worden, met minimaal 150 meter afstand tussen behandelde velden.  Dek de behandelde grond direct na toepassing af met VIF (Virtually Impermeable Film) folie gedurende een periode van tenminste 14 dagen.…”
Section: Monitoringstechniekenunclassified
“…Of course, there is a chance for herbicide savings by using site specific herbicide application. The results of Gerhards et al (1997) demonstrated that the site specific weed management was technically feasible but further investigations are needed to verify and evaluate site specific weed control methods. The site-specific herbicide application presumes, that the herbicide spray can be omitted at certain areas within the field with no or low weed infestation.…”
Section: Introductionmentioning
confidence: 96%